Implementing nature-based solutions for creating a resourceful circular city. Issue 1 (4th March 2020) - Langergraber, Guenter; Pucher, Bernhard; Simperler, Lena; Kisser, Johannes; Katsou, Evina; Buehler, Devi; Mateo, Mari Carmen Garcia; Atanasova, Nataša
Abstract: Resource depletion, climate change and degradation of ecosystems are challenges faced by cities worldwide and will increase if cities do not adapt. In order to tackle those challenges, it is necessary to transform our cities into sustainable systems using a holistic approach. One element in achieving this transition is the implementation of nature-based solutions (NBS). NBS can provide a range of ecosystem services beneficial for the urban biosphere such as regulation of micro-climates, flood prevention, water treatment, food provision and more. However, most NBS are implemented serving only one single purpose. Adopting the concept of circular economy by combining different types of services and returning resources to the city, would increase the benefits gained for urban areas. The COST Action Circular City aims to establish a network testing the hypothesis that: ' A circular flow system that implements NBS for managing nutrients and resources within the urban biosphere will lead to a resilient, sustainable and healthy urban environment '. In this paper we introduce the COST Action Circular City by describing its main objectives and aims. The paper also serves as introduction to the review papers of the Action's five Working Groups in this Special Issue.